EVALUATION OF LETROZOLE THERAPEUTIC EFFECT IN INFERTILE WOMEN - F. Akbary-Asbagh; Z. Heidar; F. Frozan-Fard; K. Nouri; O. Azmodeh; A. Ghasemynejad; N. Salsabily M. Amirian (Acta Medica Iranica, 2007)
"nCombination therapy with clomiphene citrate plus gonadotropin (clomiphene citrate plus HMG) in induction ovulation reduce the gonadotropins dose but antiestrogenic effect of c.c. can decrease pregnancy rate. In a randomized clinical trial we compared 3 treatment protocol for induction ovulation and intra uterine insemination (I/o plus IUI) in women with infertility history more than one year, normal hysterosalpingogram (HSG), normal spermiogram and follicular stimulating hormone (FSH) < 10 IU/ml. 52 women were taken clomiphene citrate plus HMG, 52 women were received letrozole plus HMG and 28 women were taken HMG alone. Gonadotropin dose for induction ovulation in clomiphene citrate plus HMG group [mean 4.9 (1.5)] and letrozole plus HMG group significantly was lower than HMG group [mean 11 (4.5)](P < 0.05). Although size and number of mature follicule in 3 group were equal. In clomiphene citrate plus HMG group endometrial thickness was lower but level of estradiol obviously was higher than others (P < 0.05). Pregnancy rate in letrozole plus HMG group was 28%, in clomiphene citrate plus HMG group was 23% and in HMG group was 25%. In conclusion aromatase inhibitors like letrozole same as clomiphene can reduce gonadotropin dose in induction ovulation without anti estrogenic effect.